Improving student biology learning outcomes through guided inquiry assisted mind mapping - Uswatun Hasanah; Miza Nina Adlini (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2022)
Guided inquiry can make students active in solving problems with the skills and knowledge that students have. This supports the improvement of student learning outcomes and fosters student creativity in understanding learning materials through mind mapping. The purpose of this study was to examine the guided inquiry model with the aid of mind mapping on the biology learning outcomes of class X high school students. This type of research uses a quasi-experimental with Pre-test and Post-test Non Equivalent Control Group Design. The population of the study was class X students as many as 3 classes with a total of 108 people. The sample consisted of 2 classes, namely X IPA1 as the control class and X IPA2 as the experimental class. Samples were taken using purposive sampling technique. The data was taken using a test instrument in the form of multiple choice questions 20 questions. Data analysis was carried out using the t test, the results obtained were tcount> ttable so H0 was rejected and Ha was accepted. The conclusion of this study is that there is an effect of guided inquiry model with mind mapping on biology learning outcomes. This guided inquiry learning model with mind mapping can help students participate in the learning process and observation and can make students understand the subject matter better.Abstrak Inkuiri terbimbing dapat membuat siswa aktif dalam memecahkan masalah dengan keterampilan dan pengetahuan yang dimiliki siswa. Hal ini mendukung peningkatan hasil belajar siswa dan menumbuhkan kreatifitas siswa dalam memahami materi pembelajaran melalui mind mapping. Tujuan penelitian ini untuk melihat model inkuiri terbimbing berbantuan mind mapping terhadap hasil belajar biologi siswa kelas X SMA. Jenis penelitian menggunakan quasy experimental dengan Pre-test and Post-test Non Equivalent Control Group Design. Populasi dari penelitian adalah siswa kelas X sebanyak 3 kelas dengan jumlah 108 orang. Sampel terdiri atas 2 kelas yakni X IPA1 sebagai kelas kontrol dan X IPA2 sebagai kelas eksperimen. Sampel diambil menggunakan teknik purposive sampling. Data diambil menggunakan instrumen tes berupa soal pilihan berganda berjumlah 20 soal. Analisis data dilakukan dengan menggunakan uji t, diperoleh hasil thitung> ttabel jadi H0 ditolak dan Ha diterima. Kesimpulan dari penelitian ini adalah ada pengaruh model inkuiri terbimbing dengan mind mapping terhadap hasil belajar biologi. Model pembelajaran guided inquiry dengan mind mapping ini bisa membantu siswa berpartisipasi dalam proses pembelajaran maupun pengamatan serta dapat membuat siswa lebih memahami materi pelajaran.